2021
DOI: 10.1080/22221751.2021.2004864
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of active tuberculosis in patients with rheumatic diseases: a multi-center, cross-sectional study in China

Abstract: Evidence of active tuberculosis (ATB) in patients with rheumatic diseases are research priorities but limited data from China have been reported. Research targeting patients not taking anti-TNF biologics are especially insufficient. We aimed to investigate the prevalence and risk factors of ATB in this at-risk population. We conducted a tertiary hospital-based, multi-center, cross-sectional study by using stratified multi-stage cluster sampling strategy to screen ATB in patients with rheumatic diseases. We est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Among 27 studies, nine were from China, 7,8,11,12,[20][21][22][23][24] and the rest were in various countries 1,[4][5][6]9,[14][15][16][25][26][27][28][29][30][31][32][33][34] (Table 1). Twenty-five studies reported prevalence of TB disease, [4][5][6][7][8][9]11,12,[14][15][16]20,21,[23][24][25][26][27][29][30][31][32][33][34] whereas three studies ...…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 27 studies, nine were from China, 7,8,11,12,[20][21][22][23][24] and the rest were in various countries 1,[4][5][6]9,[14][15][16][25][26][27][28][29][30][31][32][33][34] (Table 1). Twenty-five studies reported prevalence of TB disease, [4][5][6][7][8][9]11,12,[14][15][16]20,21,[23][24][25][26][27][29][30][31][32][33][34] whereas three studies ...…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…We grouped the country origin based on WHO global list of high TB burden countries. 36 There were 17 studies from 5 high TB burden countries [6][7][8]11,12,15,[20][21][22][23][24][25]27,29,[31][32][33] and 8 studies from 7 non-high TB burden countries. 4,5,9,14,16,26,30,34 There was an apparent higher prevalence of TB disease in high TB burden than non-high TB burden countries: active TB (5% vs 2%), pulmonary TB (3% vs 1%), extrapulmonary TB (3% vs 0%), and disseminated TB (1% vs 0%).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few systematic studies have been reported on rheumatic diseases concomitant with TB; however, most were singledisease studies and included few observational indicators (13)(14)(15)(16)(17)(18)(19). In this study, we investigated the clinical manifestations and influencing factors of TB among patients with various common rheumatic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have reported inconsistent results regarding the specific incidence and prevalence of SLE-TB (10)(11)(12)(13). Therefore, a contemporary and comprehensive evaluation and update of the SLE-TB epidemiology data worldwide is necessary as it will provide a theoretical basis for TB screening and preventive treatment in SLE patients.…”
Section: Introductionmentioning
confidence: 99%